2020
DOI: 10.3389/fvets.2020.00318
|View full text |Cite
|
Sign up to set email alerts
|

Pre-conditioning of Equine Bone Marrow-Derived Mesenchymal Stromal Cells Increases Their Immunomodulatory Capacity

Abstract: Mesenchymal stem/stromal cells (MSCs) are increasingly explored for the treatment of degenerative and inflammatory diseases in human and veterinary medicine. One of the key characteristics of MSCs is that they modulate inflammation mainly through the secretion of soluble mediators. However, despite widespread clinical use, knowledge regarding the effector mechanisms of equine MSCs, and consequently their effectiveness in the treatment of diseases, is still unknown. The objectives of this study were to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 80 publications
3
17
0
Order By: Relevance
“…Tumor necrosis factor-alpha (TNF-α) priming led to an upregulation of immunoregulatory factors. The priming of MSCs with several inflammatory cytokines may have additional effects, as shown with the combination of IFN-γ and TNF-α in a recent study [ 42 ]. Human MSCs stimulated with interleukin (IL)-1β, IL-6, and IL-23 produced higher levels of transforming growth factor-beta (TGF-β) than the unstimulated MSCs [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor-alpha (TNF-α) priming led to an upregulation of immunoregulatory factors. The priming of MSCs with several inflammatory cytokines may have additional effects, as shown with the combination of IFN-γ and TNF-α in a recent study [ 42 ]. Human MSCs stimulated with interleukin (IL)-1β, IL-6, and IL-23 produced higher levels of transforming growth factor-beta (TGF-β) than the unstimulated MSCs [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Equine studies have reported different results regarding iNOS2 participation. Carrade et al ( 4 ) described that NO production by equine MSCs varies from different tissue sources, and subsequent studies have shown that iNOS2 inhibition does not change the inhibitory effect of equine MSCs on lymphocyte proliferation ( 26 , 30 , 42 ). IDO1 activity does not seem to be involved in the capacity of equine MSCs to inhibit allogeneic lymphocyte proliferation ( 26 ) but may participate in maintaining this suppressive effect ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Carrade et al ( 4 ) described that NO production by equine MSCs varies from different tissue sources, and subsequent studies have shown that iNOS2 inhibition does not change the inhibitory effect of equine MSCs on lymphocyte proliferation ( 26 , 30 , 42 ). IDO1 activity does not seem to be involved in the capacity of equine MSCs to inhibit allogeneic lymphocyte proliferation ( 26 ) but may participate in maintaining this suppressive effect ( 42 ). In addition to soluble mediators, cell–cell interactions between MSCs and lymphocytes via adhesion molecules may increase the effectiveness of the MSC immunomodulation ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, untreated MSC are transplanted in the spinal cord, which could cause sudden environmental shock for the cells. Other MSC priming methods (i.e., cytokines, hypoxia, antioxidants, chemical drugs) have been used to increase their therapeutic efficacy in a variety of tissues, resulting in enhanced repair [20,[68][69][70][71]. However, the effect of those priming methods on transplant survival are varied or not always presented.…”
Section: Msc Primingmentioning
confidence: 99%
“…However, the effect of those priming methods on transplant survival are varied or not always presented. A culture of MSC with IFNγ and TNFα added to the medium increases MSC immunomodulatory activity [21,23,68,72]. Pre-treatment of MSC with antioxidants, such as melatonin or all-trans retinoic acid, results in upregulation of the survival gene, bcl2, and increased MSC proliferation and wound healing efficacy, respectively [69,70].…”
Section: Msc Primingmentioning
confidence: 99%